Programa de intervenção com bebês pré-termo e suas famílias: avaliação e subsídios para prevenção de deficiências - Formiga, Cibelle Kayenne Martins Roberto (Universidade Federal de São Carlos, 2003)
Early identification of developmental delays in preterm infants is notable in various studies which emphasize the prevention of disabilities through the possibility of a better prognosis through specialized special education services or other rehabilitation measures. Intervention programs emphasize the integration of parental participation so they may take on coresponsibility for their children's development as an integral part of the treatment. The objective of this research was to evaluate the effectiveness of a program of early intervention with babies preterm with and without the parents' training. The participants in this study were 8 preterm infants with an average gestational age of 32 weeks and an average chronological age of 3 months and 6 days and their respective families. The study was done at the Neuropediatric Physiotherapy Unit at UFSCar and approved by the University Research Ethics Committee. The experimental research method was used and the participants were randomly divided into two separate groups: Control and Experimental. The Control Group was composed of 4 infants who received physiotherapy treatment but whose parents did not receive any orientation or training to work with their children at home. The Experimental Group was composed of 4 infants who received physiotherapy treatment and whose parents received orientation and training to continue the physiotherapy program at home. This four month study utilized the Operational Portage Inventory (OPI) and the Alberta Infant Motor Scale (AIMS) to measure the infants'development. All data from evaluation charts and videotapes of monthly evaluations and weekly sessions were registered and analyzed for two aspects: infant and parent behavior. The categories for the analysis of motor sensory development were in accord with the items proposed in AIMS and the training items were in accord with the OPI. The statistical treatment utilized the regression method to compare the evolution between the control and experimental groups. Analysis of parent participation in the intervention program was evaluated in three aspects: behaviors installed in the mediators, the performance of mediators as observers and the mediators opinion of the intervention program. The results demonstrated that both groups had significant improvement in all developmental areas analyzed and when compared to each other, the experimental group's evolution was superior to the control group. In relation to family participation in the program, the results verified that parents in the experimental group demonstrated a good level of involvement with behavior in installed in relation to training with the infant and both groups demonstrated satisfaction in participation in the study based on the evolution obtained by their children. Based on these results it can be stated that the participation of parents associated with the intervention program significantly benefited the sensory motor development of the infants in the present study.
Keywords: Educação especial de zero a seis meses; Fisioterapia; Desenvolvimento neuro - sensório - motor; Orientação de mães; Preterm infant; Neurosensory-motor development; Early intervention; Physiotherapy; Parent participation; Prevention of disabilities; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL